Social Media Usage Patterns by Klungkung Regional Tourism Authority During 2023 Recovery Period: A Content Analysis - Purnawan, Ni Luh Ramaswati; Pitana, I Gde (INJECT (Interdisciplinary Journal of Communication), 2026)
While government authority has a vital role in tourism management and destination marketing, social media serves as an essential tool in tourism communication and promotion. The shifts in consumer digital behavior, especially in the aftermath of the pandemic, created potential and challenges for government authorities to embrace social media in driving tourism recovery. This study explores the social media usage pattern of local government in post-pandemic tourism recovery, focusing on the Klungkung Regional Tourism Authority. Using content analysis methodology, social media posts were studied from official social media accounts of the authority (Facebook, Instagram, YouTube, and TikTok) from January to April 2023. The result indicated that while the authority maintains its online presence on multiple platforms, engagement strategies remain suboptimal, marked by irregular posting patterns, low interactivity, and inconsistent hashtag usage. This study also revealed a significant gap in platform popularity and actual usage effectiveness. This study contributes to social media in tourism promotion literature, and the practical implications are discussed.